Transformasi Negasi Dimensi Kehambaan Pengamal Sholawat Wahidiyah dan Implementasinya pada Lembaga Pendidikan Formal - Zumrotul Mukaffa (Islamica: Jurnal Studi Keislaman, 2017)
This article examines the disappearance of the dimension of servitude among the members Sholawat Wahidiyah. The results of this study indicate that the variety of human normative responsibilities as a manifestation of the dimension of servitude to God (takÄlif) is valid for negation without reducing the degree of obedience. The validity of the negation occurs when the members are on their spiritual journey in the phase of fÄnÄ« al-majdhÅ«b. The provisions of the validity of the negation depend on the time of the phase of the journey. Practitioners who have arrived at this degree are totally free from all their responsibilities theo-centrically, as servants who are bound by devotion to their Lord. The validity of the negation refers to the mystical perspective and experience of prominent sufis, such as Ibn â€˜ArabÄ« and â€˜Abd al-WahÄb al-Shaâ€˜rÄnÄ«. As an inseparable part of mujÄhadah, the doctrine of fÄnÄ« al-majdhÅ«b is also transformed into a formal education environment managed by the practicioners Sholawat Wahidiyah. Thus, this doctrine is not only projected for members who have been mature in terms of age and spiritual journey, but also for students at the elementary and secondary levels of education.